Radiation Stricture of the Biliary Ducts: An Emerging New Entity?. Issue 4 (1992) - Halevy, A.; Adam, A.; Stamp, G.; Benjamin, I. S.; Blumgart, L. H.
Abstract : Two patients with stricture of the extrahepatic biliary tree are described. Both patients presented with a clinical picture of obstructive jaundice one to two years following radiotherapy for a malignant condition. As no recurrent tumour was detected in either of the patients the strictures were considered to be the result of radiation therapy. Bilio-enteric decompression was performed in both patients who are well at follow up one and ten years after the procedure.